A Comprehensive Approach to the Professional Development of Specialists of Guardianship and Guardianship Authorities in Relation to Minors - Semya, G.V.; Lashkul, M.V.; Yarovikova, O.A. (Psihologičeskaâ nauka i obrazovanie, 2023)
The article discusses the relevance and grounds for the creation of a comprehensive system of professional development of specialists of guardianship and guardianship (OOIP) in relation to minors who are state and municipal employees. Currently, there is no system of specialized professional training of OOIP specialists within the framework of secondary and higher education. The article analyzes the experience of conducting advanced training courses and the work of the only master's degree in the country in the direction of "Specialist OOIP in relation to minors", which combines two models: "inconsistent", since there is no consistent bachelor's degree, and "advanced training", designed for people who already have work experience. The conducted research on a sample of 1080 OOIP specialists revealed the specifics of their work, psychological well-being, educational needs, and the relevance of master's degree studies. The analysis of professional development programs showed that psychological and pedagogical disciplines occupy about 50% of the volume. The study revealed the presence of new trends: confessional competencies required to work with families of different faiths, competencies in the field of digitalization of specialists' activities, mediation skills, the ability to work in an interdepartmental and multidisciplinary team, the ability to identify the opinion of a child of any age on issues affecting his interests are in demand. It is shown that the system of training of OOIP specialists includes professional and personal self-development and self-improvement, one of the forms of which are professional skill contests. The innovation of recent years has been the creation of resource centers in the regions that provide methodological support, consulting, organization and maintenance of a closed group in a social network, supervision, training events for OOIP specialists. It is recommended to include in the regional professional development programs, in addition to advanced training courses, other elements of the personnel management system: planning, organization, selection, motivation, stimulation, control, as well as career management of OOIP specialists. В статье обсуждаются актуальность и основания для создания комплексной системы профессионального развития специалистов органов опеки и попечительства (ООиП) в отношении несовершеннолетних граждан, которые являются государственными и муниципальными служащими. В настоящее время отсутствует система профильной профессиональной подготовки специалистов ООиП в рамках среднего и высшего образования. Анализируется опыт проведения курсов повышения квалификации и работы единственной в стране магистратуры по направлению «Специалист ООиП в отношении несовершеннолетних», которая объединяет в себе две модели: «непоследовательную», так как отсутствует последовательный бакалавриат, и «повышающую квалификацию», рассчитанную на людей, уже имеющих опыт работы. Проведенное исследование на выборке 1080 специалистов ООиП позволило выявить специфику их работы, психологическое самочувствие, образовательные потребности, актуальность обучения в магистратуре. Анализ программ повышения квалификации показал, что психолого-педагогические дисциплины занимают около 50% объема. Исследование выявило наличие новых трендов: востребованы конфессиональные компетенции, необходимые для работы с семьями разных конфессий, компетенции в сфере цифровизации деятельности специалистов, навыки медиации, умения работать в межведомственной и полидисциплинарной команде, умение выявить мнение ребенка любого возраста по вопросам, затрагивающим его интересы. Показано, что система подготовки специалистов ООиП включает профессионально-личностное саморазвитие и самосовершенствование, одной из форм которого являются конкурсы профессионального мастерства. Новацией последних лет стало создание в регионах ресурсных центров, осуществляющих методическое сопровождение, консультирование, организацию и ведение закрытой группы в социальной сети, проведение супервизии, обучающих мероприятий для специалистов ООиП. Рекомендовано включить в региональные программы профессионального развития, помимо курсов повышения квалификации, другие элементы системы управления кадрами: планирование, организацию, отбор, мотивацию, стимулирование, контроль, а также управление карьерой специалистов ООиП.